Gastrointestinal influences in multiple sclerosis: Focus on the role of the microbiome. (8th March 2018) - Francis, Anna; Constantinescu, Cris S.
Abstract: Despite extensive research, the etiology of multiple sclerosis remains unclear. Gene–environment interactions are believed to determine the risk of disease, but the necessary exposures have not been identified. Here, we review the evidence for the role of disturbances in the normal intestinal flora (the gut microbiome) in the pathogenesis of multiple sclerosis. We present data from human and animal studies proposing that the intestinal immune system integrates bacterial signaling with systemic inflammatory and regulatory responses. Dysbiosis, which is observed more frequently in multiple sclerosis than in health, can skew the intestinal T‐cell repertoire towards an effector T‐cell response, which is subsequently amplified in different tissues. In patients with a genetically determined predisposition, this could lead to inflammation and demyelination in the central nervous system. Furthermore, bacterial products can directly affect the blood–brain barrier, neurons and microglia, and bacterial antigens that mimic neuro‐antigens can lead to activation and proliferation of autoreactive T cells.